Clinical analysis of cases of precancer of the oral mucosa and the red border of the lip - Irina K. Lutskaya (LLC "MEDIAFORMAT", 2024)
Early detection of diseases prone to malignancy is one of the most important problems in medicine. Elements of lesions on the mucous membrane of the oral cavity and the red border of the lips, characterized by a risk of degeneration, are available for visual inspection and can be detected during a general examination of the patient by a doctor of any specialty. A qualified description of clinical cases helps to familiarize specialists working in healthcare institutions with the clinical manifestations of pathology.